Intra‐Valve Elemental Distributions in Arctic Marine Ostracodes: Implications for Mg/Ca and Sr/Ca Paleothermometry. (23rd February 2021) - Rodriguez, Maximiliano; Doherty, John M.; Man, Ho Lai Hilary; Wang, Rujian; Xiao, Wenshen; Zhou, Baochun; Thibodeau, Benoit; Not, Christelle
Abstract: Reconstructing intermediate and bottom‐water temperature in the Arctic Ocean is key for understanding paleoclimatic phenomena, such as the region's interactions with warm Atlantic waters, stratification, and sea‐ice dynamics. However, benthic proxy archives are sparse throughout the Arctic circle compared to lower latitudes. Trace‐element ratios (E/Ca) derived from ostracodes, a group of bivalved microscopic crustaceans, have shown promise in this regard. Samples for E/Ca measurements typically require rigorous cleaning prior to analysis, and signs of contamination are routinely monitored through the presence of other trace elements such as Al, Fe, and Mn, which are associated with suspected sources of overprinting. However, there has not yet been an intra‐valve investigation of all of these trace elements, which may hinder our ability to effectively identify geochemical overprinting. Here, we present several elemental concentration and E/Ca ratio measurements in two ostracode genera, Krithe and Polycope, extracted from Chukchi Sea sediment samples. We further investigate the intra‐valve distribution of elements within single shells of adult and juvenile specimens using electron probe microanalysis (EPMA). Our findings suggest that brushing and bleach treatments may not be effective for completely eliminating clays from the edges of valves, which can bias paleoclimatologically relevant trace‐element proxies such as Mg/Ca ratios, particularly in the case of incomplete or small samples with low amounts of calcite material. In addition, we report the first trace‐element data from the genus Polycope, which shows potential as a new Arctic paleotemperature archive. Key Points: Brushing and bleach treatments fail to completely remove external contaminants from valve edges and might compromise E/Ca measurements Incomplete or juvenile Krithe samples often yield less reproducible E/Ca measurements Polycope ostracodes show promise for Arctic paleotemperature reconstructions